2014
DOI: 10.1097/nne.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Lead Faculty Workload Model

Abstract: Teaching more efficiently while maintaining quality and consistency of course offerings is imperative in nursing education. At odds with this goal for nursing faculty are increased workloads impacted by trends to provide more distance learning, the faculty shortage, and pressure to produce more nurses at all educational levels. The Lead Faculty Workload Model updates current methods of evaluating workload and formalizes the role of lead faculty members and supporting faculty members with current expectations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…They perceived this time was not valued by leadership, particularly when they were not compensated in their workload calculation. These results align with findings from other studies 11,12. The original workload task force recommended that workload credit be allocated for the coordinator role.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…They perceived this time was not valued by leadership, particularly when they were not compensated in their workload calculation. These results align with findings from other studies 11,12. The original workload task force recommended that workload credit be allocated for the coordinator role.…”
Section: Discussionsupporting
confidence: 88%
“…Coaches are used for online courses with multiple sections that are offered in 5- or 7-week sessions. Previous research suggests additional teaching time is required for online courses 12. Study participants also identified faculty responsibilities beyond teaching such as advising the DNP students, mentoring and precepting students and new faculty members, and accepting multiple nonacademic assignments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other models in the literature were based on specific situations. For example, Waldrop and Chase22 devised a workload model for lead faculty responsible for coordinating a course and a separate model for supporting faculty who taught a course but were not responsible for coordination. This initiative was to remove inequities between faculty members responsible for all aspects of a course with several sections and faculty members who teach 1 section of the same course.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Faculty workload calculations are based on the mission of the academic setting and traditionally consider the 3 areas of teaching, research, and service. 13 A variety of workload calculation formulas have been reported 1,2,[4][5][6][14][15][16][17][18][19][20][21][22][23] in an attempt to capture the amount of time a faculty member spends in each area. The inherent difficulty of formulas accurately depicting workload is related to variables such as the type of position (tenured, tenure track, adjunct, clinical, visiting professor) and the method of course delivery (face-to-face, online, clinical, or simulation).…”
Section: Literature Reviewmentioning
confidence: 99%